2013
DOI: 10.4102/ajod.v2i1.63
|View full text |Cite
|
Sign up to set email alerts
|

Policy implementation in wheelchair service delivery in a rural South African setting

Abstract: BackgroundWheelchairs allow users to realise basic human rights and improved quality of life. South African and international documents guide rehabilitation service delivery and thus the provision of wheelchairs. Evidence indicates that rehabilitation policy implementation gaps exist in rural South Africa.ObjectivesThe aim of this article was to explore the extent to which wheelchair service delivery in a rural, remote area of South Africa was aligned with the South African National Guidelines on Provision of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…For example, research on wheelchair provision in South Africa found that lack of knowledge among provincial managers about the practical challenges was a leading cause of the lack of implementation of the assistive device mandates of the CRPD as well as the South African Department of Health Guidelines. 23 …”
Section: Resultsmentioning
confidence: 99%
“…For example, research on wheelchair provision in South Africa found that lack of knowledge among provincial managers about the practical challenges was a leading cause of the lack of implementation of the assistive device mandates of the CRPD as well as the South African Department of Health Guidelines. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Appreciating the commitment of the government to the rights of people with disabilities in provision of services 2 , the primary objective of this preliminary study was todetermine the extent of satisfaction among users of locally manufactured wheelchairs, as part of the process of monitoring social accountability Overall, the wheelchair users' satisfaction was relatively high. As with other developing countries [9][10][11][12] , participants were satisfied with wheelchair related aspects such as effectiveness of use, safety, and participation in activities, though a small proportion expressed satisfaction with service related aspects. This suggests that the locally manufactured wheelchairs were perceived to be appropriate in meeting the needs of the users.…”
Section: Eggers Et Almentioning
confidence: 96%
“…The authors however selected to focus attention on the aspects for which wheelchair users have expressed different levels of dissatisfaction. Understanding the reasons for disparities in the level of satisfaction in wheelchair users may not be easy because of the complex and multifaceted process of wheelchair service delivery 11 . Relating to satisfaction with respect to functional needs, the proportion of users who have expressed some degree of dissatisfaction in the use of personal or public transportation (41.3%) cannot be ignored.…”
Section: Eggers Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many deaf people require sign-language interpreters to reduce communication difficulties between deaf service users and hearing practitioners (Kritzinger et al 2013). In addition, wheelchair users require wheelchairs which are correctly prescribed in accordance with international and national policy guidelines (Visagie, Scheffler, and Schneider 2013).…”
Section: Disability and Health Carementioning
confidence: 99%